(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the relatively subjective character of the category «axiological modality». Both traditional and modern views concerning this category are analyzed. Communicative position of a speaker is defined by personal and typical, stereotypical items. The relativity of modality is determined by the ambiguity of the notion «reality».